Leisure time and labor productivity: A new economic view rooted from sociological perspective - Dan Cui; Xiang Wei; Dianting Wu; Nana Cui; Peter Nijkamp (Kiel Institute for the World Economy (IfW), 2018)
Most economists measure labor productivity based on activities conducted at places of work and do not consider leisure time in their calculations. In contrast, psychologists and sociologists argue that leisure has a positive role in the production process: leisure can improve individuals' labor productivity by affecting their self-development. Using empirical data from 21 OECD countries, this study finds that leisure time has a dual effect on labor productivity in terms of per capita per hour GDP. Moreover, leisure time is nonlinearly associated with labor productivity (inverted U-shaped). When leisure time reaches the optimal level (5813 hours), leisure has a compensatory effect on work and can positively influence labor productivity, but when leisure time exceeds the optimal value, leisure has a substitution effect on work and can negatively influence labor productivity.
Keywords: D24; D61; 330; leisure time; labor productivity; per capita per hour GDP; dual effect; curvilinear relationship